Work Ethics in Japanese Culture - Kedjour, Antar (The journal of contemporary issues in business and government, 2022)
The civilized renaissance of any nation determines the parameters of its success from its failure, the culture of the country, and its moral reference. The work ethic in Japanese culture was distinguished by its validity and effectiveness on the ground, with evidence that these days have proven this to be true, because it is the one that pulled Japan in the modern era out of the era of underdevelopment, and brought it into the era of development and prosperity, and it is the one that rebuilt the destroyed Japan after the Second World War, and made it in Ranks of developed countries, despite Japan's poverty of natural resources. To this day, the ethical values of work in Japanese culture still prove their validity, and force the world to respect them, and the need to adopt them, after capitalism failed to prove its validity, and it contributed to the destruction of many moral values called for by instinct and human need, such as group spirit, sacrifice, When it is lost, the person is lost with it.